Bcl-xL protects adult septal cholinergic neurons from axotomized cell death - Blömer, U. (The National Academy of Sciences, 1998)
Bcl-xL suppresses apoptotic cell death induced by diverse stimuli in cell lines in vitro. To examine the mechanism by which axotomized cholinergic neurons die in vivo, lentiviral vectors expressing Bcl-xL, human nerve growth factor (hNGF), or green fluorescent protein were injected into the septum 3 weeks before transection of the fimbria fornix. Three weeks after transection, Bcl-xL- and hNGF-injected animals showed significantly higher numbers of spared cholinergic neurons compared with control (green fluorescent protein) injected animals. These results provide evidence that adult axotomized cholinergic neurons die of apoptotic death that can be prevented by local delivery of hNGF or intracellular delivery of Bcl-xL.